Development of students' stress resistance as a necessary condition for modern reality - Kryvoshei, Kyrylo Yu.; Belyaev, Sergiy B.; Кривошей, Кирило Юрійович; Бєляєв, Сергій Борисович (Запоріжжя : Хортицька національна навчально-реабілітаційна академія, 2024)
Today, it is difficult to disagree that February 24, 2022, marked a pivotal change in the daily life of Ukrainian society. The attack by the aggressor country has a destructive impact on the functioning and development of all social institutions in Ukraine. Unfortunately, the higher education system has not escaped this impact. War is an extraordinary and extreme event that leads to constant psychological stress, making it an intense and prolonged cause of distress. The ongoing influence of military conflict is a significant challenge for the entire Ukrainian education system. Addressing the adaptation of the education system to wartime conditions is a priority issue that requires immediate solutions. This adaptation is essential to ensure continuity in education and to support both students and teachers in these difficult circumstances. … Thus, the war creates new challenges for the education system. Transformations are needed to maintain the effectiveness of the education system. This applies to both ensuring the safety and accessibility of education and providing support for students' mental health. Successful adaptation of education during the war will not only maintain its quality but also ensure the development of a future generation capable of coping with the challenges of our time. The development of stress resistance in higher education students should be based on certain resources. Such resources may include psychological competence, positive personal traits, social resources, soft skills, and more.
Keywords: SOCIAL SCIENCES::Social sciences::Education; SOCIAL SCIENCES::Social sciences::Psychology; SOCIAL SCIENCES::Social sciences::Pedgogical work; psychological stress; military conflict; wartime conditions; stress resistance; sources and resources; flexible assessment systems; psychological support centers; free psychological counseling and support; extreme conditions; crisis management; psychosocial assistance; war conditions; vulnerable groups population